The Effect of Communication Skills Training and Enrichment on Social Responsiveness and Social Communication Skills of Adolescents with Autism Spectrum Disorder and their Parents - Momen , Sanaz; Khosravi , Sadrollah; Chinaveh , Mahbobeh (Shahroud Journal of Medical Sciences, 2021)
Background: Autism spectrum disorder (ASD) threatens one’s socialization ability, and a lack of social skills can cause dysfunctions and mental health problems for adolescents. This study aimed to investigate the effect of communication skills training and enrichment on social responsiveness and social communication skills of adolescents with autism spectrum disorder and their parents in Shiraz.Methods: The study method was quasi-experimental with a pre-test and post-test design and a control group. The statistical population comprised adolescents with ASD at clinics in Shiraz, Iran, in 2019. The sample was selected from adolescents who had been diagnosed with ASD by the Exceptional Education Organization of Fars Province, and the participants were randomly allocated to two experimental and control groups (n=20 per group). The research instruments included the Social Skills Improvement System Rating Scale and the Social Responsiveness Scale with the Autism Diagnostic Interview. Data were analyzed by descriptive (mean and standard deviation) and inferential statistics (multivariable analysis of covariance).Results: The results showed that the communication skills training and enrichment program did not significantly affect the parents’ social responsiveness or the adolescents’ social communication skills. However, a significant difference was found between the experimental and control groups in terms of parents’ social communication skills (Pvalue= 0.007).Conclusions: Based on research results it can be hence concluded that communication skills training and enrichment can be used to improve social communication skills in parents of adolescents with an autism spectrum disorder.Keywords: Autism, Social responsibility, Communication skills, Adolescents